2017
DOI: 10.4103/0366-6999.209895
|View full text |Cite
|
Sign up to set email alerts
|

High Staphylococcus epidermidis Colonization and Impaired Permeability Barrier in Facial Seborrheic Dermatitis

Abstract: Background:Seborrheic dermatitis (SD) is a common inflammatory skin condition. The etiology is unclear, although overgrowth of Malassezia on the skin has been suggested to cause SD. This study investigated whether colonization with Staphylococcus plays a role in facial SD, which was not well addressed previously.Methods:The study was conducted from September 1, 2011 to February 20, 2012 in the First Hospital of China Medical University. In the first phase, the study evaluated the level of transepidermal water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
2
29
1
3
Order By: Relevance
“…Here, we report that NSC treatment at W2 was able to decrease the number of SE colonies on the face by 75% compared to W0. An et al [29] have demonstrated that fusidic acid treatment, applied for 2 weeks on the face, was able to decrease the number of SE colonies from 331 to 18, achieving 95% compared to W0, whereas moisturizers increased the number of SE colonies compared to W0. It is worth mentioning that the decrease of SE colonies on the face (15.6% W1, 75% W2) was less pronounced than on the chest (92% W1, 99% W2).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report that NSC treatment at W2 was able to decrease the number of SE colonies on the face by 75% compared to W0. An et al [29] have demonstrated that fusidic acid treatment, applied for 2 weeks on the face, was able to decrease the number of SE colonies from 331 to 18, achieving 95% compared to W0, whereas moisturizers increased the number of SE colonies compared to W0. It is worth mentioning that the decrease of SE colonies on the face (15.6% W1, 75% W2) was less pronounced than on the chest (92% W1, 99% W2).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have challenged the role of Malassezia in SD in HIV‐infected patients. One study done in HIV‐positive patients showed either negative or limited growth of Malassezia . On the other hand, a significantly higher number of Malassezia was cultured from HIV‐negative patients with SD.…”
Section: A Complex Relationship With Systemic Diseasesmentioning
confidence: 99%
“…Additional bacteria that have been implicated include Corynebacterium and Propionibacterium . One study found a higher colonization rate of S. epidermidis in both HIV‐positive and HIV‐negative patients with SD . Another recent study reported that S. aureus was the most common bacterial member of the skin flora in patients with SD, proposing an etiological role for S. aureus …”
Section: Microbiota a Major Culpritmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of the disease is unclear. Current studies have shown that seborrheic dermatitis is closely related to the excessive sebum, the excessive reproduction of Malassezia furfur and Staphylococcus epidermidis ( 3 , 4 ), and the destruction of the skin barrier function ( 5 ). The application of antifungal drugs and glucocorticoids could alleviate the symptoms ( 6 , 7 ); however, long-term application will produce telangiectasia, epidermal atrophy, glucocorticoid dependence, and other adverse reactions ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%